The behaviour of N-(phenylsulfonyl)-glycine and phenacetin in a municipal sewage treatment plant: a case study - Krause, Sonja; Schöler, Heinz Friedrich (Chemosphere, 2000)
The behaviour of N-(phenylsulfonyl)-glycine (PSG) and phenacetin (PHE) in a municipal sewage treatment plant near Heidelberg, Germany, was investigated in the summer of 1997. For that purpose, 10 g of each substance was dissolved and poured simultaneously into the influent. In addition to the spiked compounds, the samples of the influent, the biological stage and the effluent were analyzed for N-(phenylsulfonyl)-sarcosine (PSS), N-methyl-N-(phenylsulfonyl)-amide (MPS), N-methyl-phenacetin, N-methyl-N-(phenylsulfonyl)-ε-aminocaproic (PSC) acid and its degradation product N-methyl-N-(phenylsulfonyl)-γ-aminobutyric (PSB) acid. Within 24 h PHE could be detected almost quantitatively in the effluent. Since N-methyl-phenacetin could not be found in any of the samples, apparently no methylation of the amino-group of PHE took place. The amount of PSG in the effluent was within 24 h 26.0 g, which is more than two fold higher than added. The decrease of PSG between biological stage and effluent and the increase of PSS within the same time correlate well. Therefore, the formation of PSS by microbial methylation of PSG in the sewage treatment plant must be assumed.
Gesehen am 06.10.2020